(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
Aims are what teachers (and learners) want to achieve in a lesson or a course. Activity in a class is planned in order to achieve these aims. A lesson aim could be for the learners to demonstrate that they understand the form or use of the passive better, or to have practised intensive reading. A course aim could be to improve the report writing skills of a group of business students.